2021
DOI: 10.1177/15327086211054049
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Geographies of Being Stranded Due to COVID-19: A Poetic Autoethnography of an International Doctoral Student

Abstract: This poetic critical autoethnography paper studies my own experiences of disrupted mobility as a Vietnamese doctoral student in New Zealand who was stuck in Vietnam. Through the lens of space and place, I investigate the issues of sense of belonging and sense of place that were reconfigured in different spaces. The article highlights my agency to reinforce and reconnect with my sense of belonging. As the article focuses on immobility, it challenges the mobility bias in international education scholarship, argu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 48 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…This phenomenon is not unique to me. According to a PhD student who was stranded in her home country, Vietnam, due to COVID-19 travel restrictions, she felt she had dual living spaces in Vietnam and New Zealand and a sense of confusion and frustrations of belonging to places and spaces in both countries at the same time (Phan, 2022, p. 7), which I argue is cognitive immobility. In their study of Polish construction workers in Norway, Erdal and Ezzati (2015, p. 1207) observed that the ‘men described their position as similar to that of sailors: temporary sojourners always returning to port, but leaving again each time’.…”
Section: Identity Place and Cognitive (Im)mobilitymentioning
confidence: 99%
“…This phenomenon is not unique to me. According to a PhD student who was stranded in her home country, Vietnam, due to COVID-19 travel restrictions, she felt she had dual living spaces in Vietnam and New Zealand and a sense of confusion and frustrations of belonging to places and spaces in both countries at the same time (Phan, 2022, p. 7), which I argue is cognitive immobility. In their study of Polish construction workers in Norway, Erdal and Ezzati (2015, p. 1207) observed that the ‘men described their position as similar to that of sailors: temporary sojourners always returning to port, but leaving again each time’.…”
Section: Identity Place and Cognitive (Im)mobilitymentioning
confidence: 99%
“…It is not yet clear what and how the performative roles played by matter and human forces shape this process of navigation from their emic views. Despite some emerging studies, they mainly pertained to doctoral students' emotional geographies (Phan, 2022) or untangled their lived experience from an ecological perspective (Wang & DeLaquil, 2020). Bearing these gaps in mind, this study recruited a group of Chinese international doctoral students (CIDS) to share their emic perceptions.…”
Section: Overview: Research On Chinese International Doctoral Student...mentioning
confidence: 99%
“…In Australia as well, have creative workers struggled with the loss of normal practices ( Flore et al, 2021 ). In overseas work ( de Borja, 2021 ) and international mobility ( Phan, 2021 ), there are new problems such as forced immobility or being stranded. The pandemic has contributed to increased inequalities, where the state of previously established careers affects the probabilities of being able to outwait the crisis ( Comunian and England, 2020 ).…”
Section: Introductionmentioning
confidence: 99%